Simultaneous acoustic stimulation of human primary and secondary somatosensory cortices using transcranial focused ultrasound - Lee, Wonhye (BMC Neurosci, 2016)
BACKGROUND: Transcranial focused ultrasound (FUS) is gaining momentum as a novel non-invasive brain stimulation method, with promising potential for superior spatial resolution and depth penetration compared to transcranial magnetic stimulation or transcranial direct current stimulation. We examined the presence of tactile sensations elicited by FUS stimulation of two separate brain regions in humans—the primary (SI) and secondary (SII) somatosensory areas of the hand, as guided by individual-specific functional magnetic resonance imaging data. RESULTS: Under image-guidance, acoustic stimulations were delivered to the SI and SII areas either separately or simultaneously. The SII areas were divided into sub-regions that are activated by four types of external tactile sensations to the palmar side of the right hand—vibrotactile, pressure, warmth, and coolness. Across the stimulation conditions (SI only, SII only, SI and SII simultaneously), participants reported various types of tactile sensations that arose from the hand contralateral to the stimulation, such as the palm/back of the hand or as single/neighboring fingers. The type of tactile sensations did not match the sensations that are associated with specific sub-regions in the SII. The neuro-stimulatory effects of FUS were transient and reversible, and the procedure did not cause any adverse changes or discomforts in the subject’s mental/physical status. CONCLUSIONS: The use of multiple FUS transducers allowed for simultaneous stimulation of the SI/SII in the same hemisphere and elicited various tactile sensations in the absence of any external sensory stimuli. Stimulation of the SII area alone could also induce perception of tactile sensations. The ability to stimulate multiple brain areas in a spatially restricted fashion can be used to study causal relationships between regional brain activities and their cognitive/behavioral outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12868-016-0303-6) contains supplementary material, which is available to authorized users.